Penegakan Hukum Pidana Terhadap Pelaku Kejahatan Tanpa Hak Membawa Senjata Tajam (Studi Putusan Nomor 3058/Pid.Sus/2021/Pn.Mdn) - Hanisyah Irani Lubis; Aulia Rosa Nasution; Muazzul Muazzul (Universitas Medan Area, 2023)
In Indonesia itself, it has imposed a ban on possessing sharp weapons that can injure other people or even actions that are carried out under the pretext of self-protection. The use of sharp weapons for which the designation is not clear has the potential to lead to acts or criminal acts that are classified as crimes. The method used in this study is normative juridical, namely a research method that examines document studies, namely by using various data such as legislation, legal theory of court decisions. Indonesia Number 12 of 1951 Article 2 paragraph (1) which states that whoever carries, controls, keeps, hides, uses a stabbing weapon, or stabbing weapon, is punished with a maximum prison sentence of ten years and criminal law enforcement against perpetrators of crimes without rights. Bringing Sharp Weapons Based on Decision No. 3058/Pid.Sus/2021/PN.Mdn can be known by the judge's verdict which gave a criminal sentence of 10 (ten) months in prison.